2021
DOI: 10.1093/cid/ciab934
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin Vs Ciprofloxacin as Oral Step-Down Treatment for Escherichia coli Febrile Urinary Tract Infections in Women: A Randomized, Placebo-Controlled, Double-Blind, Multicenter Trial

Abstract: Background We aimed to determine the non-inferiority of fosfomycin, compared to ciprofloxacin, as oral stepdown treatment for E. coli febrile urinary tract infections (fUTIs) in women. Methods This was a double-blind, randomised controlled trial in 15 Dutch hospitals. Adult women receiving 2-5 days of empirical intravenous antimicrobials for E.coli fUTI, were assigned to stepdown treatment with once-daily 3 gr fosfomycin or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
8
1
2
Order By: Relevance
“…4.1 TERAPÊUTICA ANTIBIÓTICA Considerando que as ITUs que ocorrem em mulheres são predominantemente causadas por Escherichia coli, as diretrizes recomendam para o seu tratamento antibioticoterapia de 7 a 14 dias feita de forma empírica. A dificuldade de tratamento ocorre quando existem bactérias gram-negativas multirresistentes, tendo em vista o perfil de resistência antimicrobiana, fator que limita o uso de antibióticos orais em diversas partes do mundo e implica na necessidade de implantação de antibioticoterapia intravenosa e hospitalização prolongada (TEN DOESSCHATE et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…4.1 TERAPÊUTICA ANTIBIÓTICA Considerando que as ITUs que ocorrem em mulheres são predominantemente causadas por Escherichia coli, as diretrizes recomendam para o seu tratamento antibioticoterapia de 7 a 14 dias feita de forma empírica. A dificuldade de tratamento ocorre quando existem bactérias gram-negativas multirresistentes, tendo em vista o perfil de resistência antimicrobiana, fator que limita o uso de antibióticos orais em diversas partes do mundo e implica na necessidade de implantação de antibioticoterapia intravenosa e hospitalização prolongada (TEN DOESSCHATE et al, 2022).…”
Section: Discussionunclassified
“…Assim, recente estudo avaliou se a fosfomicina de 3g em 24 horas como tratamento direcionado para ITUs de E. coli em mulheres seria não inferior à utilização de ciprofloxacina. O resultado confirmou a eficácia da fosfomicina, concluindo que essa droga figura como opção de tratamento antibiótico oral adicional para casos de ITU, principalmente quando estes apresentam resistência, intolerância ou alergia às opções existentes (TEN DOESSCHATE et al, 2022).…”
Section: Discussionunclassified
“…Fosfomycin trometamol has been traditionally used for uncomplicated cystitis 15 ; however, there is a growing interest in its potential usefulness as an oral alternative for cUTI and as oral step-down after IV treatment. 9 , 16–18 A theoretical barrier for the oral use of this drug in invasive UTI has been the low plasma levels achieved. 8 However, data from a mice model of ascending pyelonephritis suggested an unexpectedly good activity with dosing reproducing a similar AUC obtained in humans after a 3 g oral dose 19 ; the authors attributed this effect to higher-than-expected kidney concentration of fosfomycin, and increased activity at acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, a recent randomized trial found that fosfomycin trometamol was non-inferior to ciprofloxacin as oral step-down treatment in 97 women with febrile UTI, of which 50% had a bacteraemic infection. 9 To the best of our knowledge, there are no specific studies of fosfomycin trometamol performed in BUTI due to MDR E. coli , and no data are available for BUTI in men.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its propensity to cause CDI and increased resistance in TB, some clinicians prefer to avoid it. Although IDSA guidelines suggest avoiding nitrofurantoin and fosfomycin in upper UTI, a recent non-inferiority RCT suggests that fosfomycin was non-inferior to ciprofloxacin for de-escalation in febrile UTI (15). The duration of therapy can be as low as 5-7 days [12].…”
Section: ) De-escalationmentioning
confidence: 99%